The universal banking reality of the Industrial Bank through the causal relationship between the deposits of the Industrial Bank and the total loans granted - during the period (2004-2015) - عذافة حيدر حسين (Journal of Economics and Administrative Sciences, 2019)
Deposits with the Industrial Bank, together with loans received from others, are non-financial financial resources, which are sources of supply to the Industrial Bank of funds that allow the Bank to expand the granting of loans. The increases in this resource indicates that the bank is practicing comprehensive banking, which is consistent with the nature of the transformation of the banking system towards multiple businesses. Therefore, the research comes to highlight the causality of the trend between total deposits and total loans. And if the causality is found, is it one-way or two-way? How long is the impact?